Communication in Philippine folk dance of the Cordillera Region - Guzon, Ria Marie R.; Prof. Flores, Romana S. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This research described the body movements in slelcted courtship dances of the Cordilleras, which messages as a form of nonverbal communication. The Study wanted to find out what kinesics in the courtship dances of selected Cordilleran tribes communicates. The study explored the movements and techniques of Philippine Dance on order to: 1. identify the courtship dances of selected Cordilleran tribes, 2. identify the movement of the courtship dances of selected Cordilleran tribes with help from the Cordilleran choreographers, non-Cordilleran choreographers and Cordilleran students. This research foucused on 3 dances: Salip/Tupay-ya, Tayo/Tayaw, and Salissid/Lablabaan. Movement identified included arm movements mimicking a bird in a fight, namely, the eagle. Footwork included the feet shuffle, drag and hop, taken after the footwork of the rooster and hen. We are familiar with these dances since they are part of our culture. These dances are not only for entertainment but are also a part of our traditions. In terms of kinesis, these dance movements vary slightly from tribe to tribe because of their geographical location and their different beliefs. Also, these variations are due to the different attitudes of the people teaching and learning these dances. The interpretation of one may be different from another. Thus, we see these same dances executed differently. Although interpretations are different, these dances share the same meaning: courtship of the female by the male, much like the hen being pursued by the rooster. Their different movements merely distinguish one tribe from another. In terms of nonverbal communication, their messages are the same. Their dance movements are a way of interacting among themselves and with other communities, even with the rest of the world. Dance as atoll to communicate is seen in this research. Attention was given to the different factors the give rise to variations of the movements and the messages. Geography, beliefs, and evolution of the dance itself arefactors contributing to these changes.
Thesis (Bachelor of Arts in Speech Communication)--University of the Philippines Diliman